Ask Question
27 August, 09:35

Solve the system of equations using substitution

2x-3y=-1

X=y+1

+3
Answers (1)
  1. 27 August, 11:26
    0
    Substitute x = y + 1 into 2x - 3y = - 1

    2 - y = - 1

    Solve for y in 2 - y = - 1

    y = 3

    Substitute y = 3 into x = y + 1

    x = 4

    Therefore,

    x = 4

    y = 3
Know the Answer?
Not Sure About the Answer?
Find an answer to your question ✅ “Solve the system of equations using substitution 2x-3y=-1 X=y+1 ...” in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.
Search for Other Answers